(untitled) (KULT_online, 2013)
Matthias Aumüller’s 2012 Narrativität als Begriff. Analysen und Anwendungsbeispiele zwischen philologischer und anthropologischer Orientierung is a collection of essays that discuss the concept of narrativity through the lens of different disciplines: historiography, journalism, game studies, film, literature, linguistics, language acquisition, psychoanalysis, philosophy, sociology, law, and psychology. In its entirety, the book is an eclectic overview of the multifaceted nature of narrativity that serves as a solid introduction to the commonalities and differences between philologically and anthropologically oriented conceptualizations of narrativity.